Structural changes in amber due to uranium mineralization - Havelcová, Martina; Machovič, Vladimír; Mizera, Jiří; Sýkorová, Ivana; René, Miloš; Borecká, Lenka; Lapčák, Ladislav; Bičáková, Olga; Janeček, Oldřich; Dvořák, Zdeněk (Journal of environmental radioactivity, 2016)
The presence of uranium, with a bulk mass fraction of about 1.5 wt% and radiolytic alterations are a feature of Cenomanian amber from Křižany, at the northeastern edge of the North Bohemian Cretaceous uranium ore district. Pores and microcracks in the amber were filled with a mineral admixture, mainly in the form of Zr-Y-REE enriched uraninite. As a result of radiolytic alterations due to the presence of uranium, structural changes were observed in the Křižany amber in comparison with a reference amber from Nové Strašecí in central Bohemia; this was of similar age and botanical origin but did not contain elevated levels of uranium. Structural changes involved an increase in aromaticity due to dehydroaromatization of aliphatic cyclic hydrocarbons, loss of oxygen functional groups, an increase in the degree of polymerization, crosslinking of CC bonds, formation of a three-dimensional hydrocarbon network in the bulk organic matrix, and carbonization of the organic matrix around the uraninite infill.
Keywords: Molecular Structure; zkameněliny; Uranium; Amber; Fossils; plynová chromatografie s hmotnostně spektrometrickou detekcí; jantar; Česká republika; Gas Chromatography-Mass Spectrometry; molekulární struktura; Czech Republic; uran